Optimizing the synergy of strength and ductility in a Fe–18Mn–8Al–1C–5Ni lightweight steel by adjusting the distribution, volume fraction and size of B2 phases and κ-carbides - P. Li; H.L. Sun; N. Xiao; H. Ding; X.F. Guo (Journal of Materials Research and Technology)
Current study presents a way to control precipitates in a designed Fe–18Mn–8Al–1C–5Ni (wt.%) lightweight steel through annealing and aging treatment. The main objective is to obtain refined and homogeneously distributed B2 phases and intra-granular κ-carbides to enhance mechanical properties. After annealing, the microstructure consists of recrystallized austenite with polygonal B2 phases along grain boundaries (GB-B2) and intra-granular B2 phases (IG-B2). Subsequent aging leads to the newly dual-precipitation of both nanoscale IG-B2 particles and coherent κ-carbides within the grains. As a result, the aged steel exhibited a remarkable ultra-high strength (yield strength of 1220 MPa, tensile strength of 1423 MPa) and a total elongation of 35.8%. The optimized precipitation of GB-B2 (∼360 nm) and IG-B2 (∼150 nm) particles as well as coherent κ-carbides intra-granularly (∼2.6 nm) contributes to enhancing strength significantly with maintaining good ductility. Meanwhile, due to the non-shearing characteristic of GB-B2 and high-density IG-B2 particles, the investigated steel exhibits distinct enhancement of work hardening ability compared to lightweight steels reinforced with single κ-carbides precipitates. These findings provide valuable insights for designing high-performance lightweight steels by tailoring the precipitation configuration.